Defecation Behavior in Elementary School Age Children Who Live Along the Kampar River Riau Province - Zahtamal Zahtamal; Fifia Chandra; Ridha Restila; Tuti Restuastuti (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Based on WHO reports, nine out of ten people who live in rural areas still defecate carelessly. The results of an initial survey conducted in November 2018 of 46 houses along the Kampar river in the village of Buluh China Riau Province, 42% of the community still open defecation, such as into the river. This study aims to get a picture of defecation behavior in elementary school age children who live along the river. Methods: This research was conducted in Buluh Cina Village, Siak Hulu District, Kampar Regency, Riau Province which is a village close to a river. This type of research is a descriptive survey. This research was conducted in March to October 2019. The research subjects were elementary school students Buluh Cina with a total of 85 people. The instrument in this study was a questionnaire to measure knowledge, attitudes and practices related to defecation habits. Data analysis using descriptive analysis. Result and Discussion: The results showed that the median score of students' knowledge was 70 (maximum score is 100) and the average attitude score was 48. As many as 80% of students already have latrines at home, however, only 58.8% of students have defecated in their latrines, 57.6% of their latrines have clean water, soap and running water available. Conclusion: Based on the results of the study concluded that the behavior of elementary school children who live in watersheds is still not ideal and one of the causes is the unavailability of healthy latrine facilities at home